Simultaneous Stabilization of Lithium Anode and Cathode using Hyperconjugative Electrolytes for High‐voltage Lithium Metal Batteries. Issue 11 (6th February 2023) - Zhang, Haikuo; Li, Ruhong; Chen, Long; Fan, Yingzhu; Zhang, Hao; Zhang, Ruixin; Zheng, Lei; Zhang, Junbo; Ding, Shouhong; Wu, Yongjian; Ma, Baochen; Zhang, Shuoqing; et al.
Abstract: Although great progress has been made in new electrolytes for lithium metal batteries (LMBs), the intrinsic relationship between electrolyte composition and cell performance remains unclear due to the lack of valid quantization method. Here, we proposed the concept of negative center of electrostatic potential (NCESP) and Mayer bond order (MBO) to describe solvent capability, which highly relate to solvation structure and oxidation potential, respectively. Based on established principles, the selected electrolyte with 1.7 M LiFSI in methoxytrimethylsilane (MOTMS)/ (trifluoromethyl)trimethylsilane (TFMTMS) shows unique hyperconjugation nature to stabilize both Li anode and high‐voltage cathode. The 4.6 V 30 μm Li||4.5 mAh cm −2 lithium cobalt oxide (LCO) (low N/P ratio of 1.3) cell with our electrolyte shows stable cycling with 91 % capacity retention over 200 cycles. The bottom‐up design concept of electrolyte opens up a general strategy for advancing high‐voltage LMBs. Abstract : The molecule descriptors proposed in this work guide a bottom‐up hyperconjugative electrolyte design, which exhibits superior stability for both Li anode and high‐voltage cathode; and enables the 4.6 V Li||LCO full cell (30 μm Li, 4.5 mAh cm −2 LCO, low N/P ratio of 1.3) to display great performance improvement. The bottom‐up electrolyte design concept opens up a universal strategy for advancing high‐voltage lithium‐metal batteries.